화석에너지와 CO2배출량 규제 하의 경제와 환경의 효율성 분석 - 강상목; Sang Mok Kang; 조단; Dan Zhao (자원·환경경제연구, 2013)
본 연구의 목적은 2000-2009년 국가별로 환경과 화석에너지의 제약 하에서 경제와 환경의 효율을 측정하고자 함이다. 본 연구는 국가별 소득수준에 따른 OECD국가, 중고소득국가, 저소득국가 등 세 그룹으로 구분하여, 생산가능집합에서 바람직한 산출물인 GDP와 오염물을 동시에 포함한 ‘환경지향형, 경제지향형, 환경-경제지향형, Two-stage DEA모형’ 등의 네 가지 방법을 제시하여 비교한다. OECD국가는 상대적으로 경제효율성이 높으나 환경효율성은 낮았고 비OECD국가는 환경효율성이 높고 경제효율성이 낮았다. 화석에너지와 온실가스의 저감의 여지는 OECD국가가 더 높았다. The purpose of this paper is to measure economy and environment efficiencies under fossil fuel and environment regulation by countries for 2000-2009. Distinguishing 83 countries with three groups of OECD, upper-middle, and low countries, we compare four models such as environment oriented, economy-oriented, environment-economy oriented, and two-stage types, which include a desirable output, GDP and an undesirable output, pollutant together in the production possibility set. OECD countries relatively showed high economy efficiency and low environment efficiency, whereas Non-OECD countries showed high environment efficiency and low economy efficiency. OECD countries reported a higher possibility to reduce fossil fuel and CO2 emission.